Sistem Informasi Quality Assurance Proses Produksi Menggunakan Metode Agile Berbasis Web - Ernawati, Ayu; Kurnia, Dadang; Hindasyah, Achmad (Jurnal Informatika Universitas Pamulang, 2021)
The company still uses manual recording of reports, namely using paper media in production activities, so during this pandemic it is quite difficult for admins and superiors to check reports. In addition, because the reporting process is still manual, data loss or data redundancy often occurs. This research designs and creates a web-based system to assist admins and superiors in checking reports. This system can provide item status reports, good item reports, service items, and damaged items, as well as monthly sales charts. For making this application using the agile method, where the application is made by collecting data which is then made an application that goes through the phases of planning, implementation, software testing, documentation, testing and maintenance. Based on the questionnaire on the satisfaction of using the system, a minimum number of 83.33 was obtained which indicates the application is in accordance with the company's request, where data can be stored properly and can detect double input data.